Emancipatory Popular Education and overexploitation: portraits of the class struggle - Roberta Traspadini (Universidade Federal do Norte do Tocantins, 2024)
This article aims to reflect on the following problematizing questions: 1) What is popular education, what is its origin and what teachings does it provide us? 2) Why, after so many historical centuries of resistance and production of orders other than the hegemonic, does part of the critical field maintain the deviation regarding the content of popular education in its real emancipatory intention? To begin the reflective trajectory, we start with a Mexican mural-image by Alba Calderón, entitled Os desocupados. In the theoretical framework of Paulo Freire, José de Souza Martins, Claudia Korol, Oscar Jara, and the sociologist-muralist Eduardo Kingman, the reflection intends to address the questions above, to, in the end, make considerations about the centrality of popular education in the light of experience of rural social movements.